Perovskite X-ray direct detector, preparation method and application thereof
By using Ti3C2 MXene film in situ oxidation to generate TiO2 as the electron transport layer in the perovskite X-ray direct detector, and growing a two-dimensional perovskite film to form a three-dimensional heterostructure, the problem of insufficient interface coupling is solved and significantly The photoelectric performance and response speed of the detector are improved.
Patent Information
- Application Number
- CN202411348734.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-21
AI Technical Summary
The interface coupling between the electron transport layer and the perovskite layer is insufficient, resulting in limited effective collection of carriers, affecting the device's imaging clarity, response speed and real-time performance.
The Ti3C2 MXENE film is used to oxidize TiO2 as an electronic transmission layer, and it grows a high -quality two -dimensional perovskite film on it to form a three -dimensional heterogeneous structure to improve the interface coupling and the extraction efficiency of the load.
A significant improvement of the photoelectric performance and response speed of the osteotic X -ray detector, enhance the migration efficiency of the load, reduce the interface defect, and improve the sharpness of the imaging and the real -time detector.
Smart Images

Figure CN119342974A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite direct X-ray detectors, and in particular to a perovskite direct X-ray detector, a preparation method and applications thereof. Background Art
[0002] X-ray direct imaging technology is an advanced method that uses semiconductor materials to directly convert X-rays into electrical signals. Compared with traditional indirect imaging technology, direct imaging technology has significant advantages in imaging speed and image quality. The core of this technology lies in its high photoelectric conversion efficiency, which enables X-ray signals to be quickly converted into electrical signals, thereby achieving high-resolution image integration. X-ray direct imaging technology has been widely used in medical imaging, industrial non-destructive testing, safety inspection, and materials science, greatly promoting the development and practical application of related technologies.
[0003] In recent years, two-dimensional metal halide perovskites have attracted much attention due to their excellent performance. Perovskite materials exhibit extremely high X-ray absorption capabilities and can effectively capture and convert X-ray signals. At the same time, their high carrier mobility greatly improves the conduction efficiency of electrons and holes, which helps to improve the response speed of the detector. In addition, the adjustable band gap characteristics of perovskite materials provide broad space for their flexibility in different application scenarios. Precisely because of these advantages, perovskites are considered to be the preferred materials for the new generation of X-ray direct detection and have broad market prospects.
[0004] However, despite the many advantages of perovskite materials, traditional perovskite devices still face some technical challenges in practical applications. In particular, in terms of the interface coupling between the electron transport layer and the perovskite layer, the existing device design often leads to limited effective collection of carriers. Due to poor interface coupling, electrons and holes are prone to recombination at the interface, which significantly reduces the overall performance of the device, especially affecting the clarity and accuracy of imaging. In addition, the presence of interface defects will also reduce the response speed of the device, affecting the real-time performance and reliability of the detector.
[0005] Therefore, in order to promote the popularity and effectiveness of perovskite X-ray direct detectors in practical applications, it is urgent to develop a new detector structure and its preparation method. This new structure should be able to improve the interface coupling between the electron transport layer and the perovskite layer, thereby enhancing the effective collection capacity of carriers, and thus achieving higher detection performance and response speed. Only by solving these key technical problems can perovskite X-ray direct detectors truly be widely used to meet the growing market demand. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, one of the technical problems to be solved by the present invention is to provide a perovskite X-ray direct detector, the second technical problem to be solved by the present invention is to provide a method for preparing a perovskite X-ray direct detector, and the third technical problem to be solved by the present invention is to provide a specific application of a perovskite X-ray direct detector.
[0007] The inventive concept of the present invention is to use Ti 3 C 2 In situ oxidized TiO on MXene film 2 The matrix acts as an electron transport layer, and high-quality two-dimensional perovskite films are further grown on this basis to form a three-dimensional heterostructure, which enables the effective extraction of carriers in the perovskite layer, thereby significantly improving the photoelectric performance and response speed of the device.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions.
[0009] The invention discloses a perovskite direct X-ray detector, which has a structure from bottom to top of a substrate, an electron transport layer, a two-dimensional perovskite film, a hole transport layer and a metal electrode layer, wherein the electron transport layer is Ti 3 C 2 In situ oxidized TiO on MXene film 2 Matrix.
[0010] Preferably, the electron transport layer is prepared by the following method:
[0011] Substrate coating Ti 3 C 2 MXene film is oxidized with a weak alkaline oxidant solution to obtain Ti 3 C 2 / TiO 2 The thin film is the electron transport layer of the present invention.
[0012] Preferably, the electron transport layer is prepared by the following method:
[0013] 0.03ml-0.1ml (Ti) is coated per square centimeter of substrate. 3 C 2 T x )MXene thin layer dispersion, dried to obtain Ti 3 C 2 MXene films;
[0014] The 3 C 2 T x) The concentration of the MXene thin layer dispersion is 0.1 mg / ml-20 mg / ml;
[0015] In the above Ti 3 C 2 The MXene film was coated with a weak alkaline oxidant solution of 0.01-0.4 ml / cm2, left to stand at room temperature for 0.5h-72h, washed with water, and dried to obtain a partially oxidized Ti film. 3 C 2 / TiO 2 film.
[0016] Preferably, the weak alkaline oxidant solution is an aqueous solution of one or more of LiOH, NaOH and KOH, with a molar concentration of 0.2-2 mol / L. The weak alkaline oxidant solution can also be water or hydrogen peroxide.
[0017] The present invention also discloses a method for preparing a perovskite X-ray direct detector, comprising the following steps:
[0018] S1: 0.03ml-0.1ml (Ti) is coated on each square centimeter of the substrate 3 C 2 T x )MXene thin layer dispersion, vacuum dried at 50-70℃ for 2-6h to obtain Ti 3 C 2 MXene films;
[0019] S2: In the above Ti 3 C 2 The MXene film is coated with 0.01-0.4 ml / cm2 of 0.2-2 mol / L weak alkaline oxidant solution, left to stand at room temperature for 0.5 h-72 h, washed with water, and dried to obtain a partially oxidized TiO2 film. 3 C 2 / TiO 2 Thin film, which serves as an electron transport layer;
[0020] S3: coating a 2D perovskite film on the electron transport layer of S2 to obtain a two-dimensional perovskite film;
[0021] S4: Based on S3, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is coated as a hole transport layer by spraying, spin coating or blade coating;
[0022] S5: Based on S4, a layer of Au metal electrode is evaporated on the hole transport layer by an evaporation method.
[0023] Preferably, the step S3 is specifically as follows: coating the 2D perovskite aqueous solution on the electron transport layer by spraying, spin coating or blade coating, and then transferring it to a vacuum drying oven, and annealing at 100-220° C. for 3-5 hours to obtain the two-dimensional perovskite film.
[0024] Preferably, when the weak alkaline oxidant solution is an aqueous solution of one or more of LiOH, NaOH and KOH, the solution is allowed to stand at room temperature for 0.5 h to 10 h;
[0025] Preferably, when the weakly alkaline oxidant solution is water, it is allowed to stand at room temperature for 36 hours to 96 hours;
[0026] Preferably, when the weakly alkaline oxidant solution is hydrogen peroxide, it is allowed to stand at room temperature for 0.5 h to 12 h.
[0027] Preferably, the substrate described in the above steps includes but is not limited to one or more of a transistor driver circuit (TFT), a complementary metal oxide semiconductor (CMOS), an indium tin oxide (ITO) or a conductive glass.
[0028] Preferably, the thickness of the electron transport layer in the above step is 5-100 nm;
[0029] Preferably, the mass concentration of the 2D perovskite aqueous solution is 10-90wt%, and the 2D perovskite is CF 3 PhMAPbBr 3 CF 3 PcI 3 BAMAPbI 3 CF 3 BnB 3 CF 3 Phb 3 CF 3 PhM A SnBr 3 CF 3 PhMABiBr 3 FAMAPbBr 3 and FAMAPbI 3 One or more of .
[0030] Preferably, the thickness of the two-dimensional perovskite film in the above steps is 100-1000 um;
[0031] Preferably, the thickness of the hole transport layer in the above step is 5-30 nm;
[0032] Preferably, the thickness of the metal electrode in the above steps is 10-1500 nm.
[0033] The invention also discloses an application of a perovskite X-ray direct detector in the direct detection of perovskite X-rays.
[0034] Compared with the prior art solutions, the present invention has the following advantages:
[0035] 1) The invention uses coated Ti 3 C 2 In-situ generation of TiO by oxidation of the surface of MXene films 2 The film acts as an electron transport layer. 3 C 2 / TiO 2 The heterostructure not only has TiO 2 The electron transport layer characteristics also retain a certain toughness and interface contact of the MXene film, which can effectively strengthen the interface coupling between the electron transport layer and the two-dimensional perovskite film and significantly reduce interface defects.
[0036] 2) The present invention seamlessly embeds two-dimensional perovskite into Ti 3 C 2 In situ oxidation of TiO on MXene surface 2 In the structural network, a composite structure with both mechanical stability and excellent optoelectronic properties is created. 3 C 2 In situ generated TiO on MXene surface 2 The network structure acts as an n-type charge collector, which can effectively extract carriers from the two-dimensional perovskite layer, and at the same time, a pin diode structure is constructed through the p-type top electrode to achieve the current-voltage characteristics of rectification. This structure not only solves the charge collection limitation problem caused by organic components, but also significantly improves the optoelectronic performance and response speed of the device.
[0037] 3) Ti 3 C 2 The structure of MXene is a two-dimensional nanosheet. Its excellent film-forming property and density can achieve better interface contact with the substrate, which is beneficial to the efficient transfer of electrons from the electron transport layer to the substrate.
[0038] 4) The present invention is simple to operate, highly practical, has abundant raw material sources, and can be mass-produced. In addition, the 3D heterogeneous structure X-ray detector constructed by the present invention has excellent performance, exhibits good sensitivity and stability, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic structural diagram of a new type of perovskite X-ray direct detector according to Example 1 of the present invention.
[0040] Figure 2is Ti in Example 1 of the present invention 3 C 2 / TiO 2 Scanning electron microscope image of the heterostructure electron transport layer.
[0041] Figure 3 is Ti in Example 1 of the present invention 3 C 2 XRD pattern after oxidation.
[0042] Figure 4 Schematic diagram of X-ray response of a novel perovskite X-ray direct detector in Example 1 of the present invention and a conventional X-ray direct detector in Comparative Example 1.
[0043] Figure 5 is Ti in Example 2 of the present invention 3 C 2 / TiO 2 Scanning electron microscope image of the heterostructure electron transport layer.
[0044] Figure 6 Schematic diagram of X-ray response of a new type of perovskite X-ray direct detector in Example 2 of the present invention and a conventional X-ray direct detector in Comparative Example 2.
[0045] Figure 7 Schematic diagram of X-ray response of a new type of perovskite X-ray direct detector in Example 3 of the present invention and a conventional X-ray direct detector in Comparative Example 3. DETAILED DESCRIPTION
[0046] In order to further highlight the innovation and practical value of the present invention, the present invention will be described in detail below in conjunction with embodiments and drawings. The protection scope of the present invention includes but is not limited to the following embodiments.
[0047] A method for preparing a perovskite X-ray direct detector comprises the following steps:
[0048] S1: 0.03ml-0.1ml (Ti) is coated on each square centimeter of the substrate 3 C 2 T x )MXene thin layer dispersion, vacuum dried at 50-70℃ for 2-6h to obtain Ti 3 C 2 MXene film; specifically, the substrate includes but is not limited to one or more of a transistor driver circuit (TFT), a complementary metal oxide semiconductor (CMOS), indium tin oxide (ITO) or a conductive glass;
[0049] S2: In the above Ti 3 C 2The MXene film is coated with 0.01-0.4 ml / cm2 of 0.2-2 mol / L weak alkaline oxidant aqueous solution, left to stand at room temperature for 0.5h-72h, washed with water, and dried to obtain a partially oxidized Ti 3 C 2 / TiO 2 The film is used as an electron transport layer; specifically, when the weak alkaline oxidant solution is an aqueous solution of one or more of LiOH, NaOH and KOH, it is allowed to stand at room temperature for 0.5h-10h; when the weak alkaline oxidant solution is water, it is allowed to stand at room temperature for 36h-96h; when the weak alkaline oxidant solution is hydrogen peroxide, it is allowed to stand at room temperature for 0.5h-12h; the thickness of the electron transport layer is controlled to be 5-100nm;
[0050] S3: coating a 2D perovskite film on the electron transport layer of S2 to obtain a two-dimensional perovskite film; preferably, the S3 step is specifically as follows: coating the 2D perovskite aqueous solution on the electron transport layer by spraying, spin coating or scraping, and then transferring it to a vacuum drying oven, annealing at 100-220°C for 3-5h to obtain the two-dimensional perovskite film; controlling the thickness of the two-dimensional perovskite film to be 100-1000um; specifically, the mass concentration of the 2D perovskite aqueous solution is 10-90wt%, and the 2D perovskite is CF 3 PhMAPbBr 3 CF 3 PcI 3 BAMAPbI 3 CF 3 BnB 3 CF 3 Phb 3 CF 3 PhM A SnBr 3 CF 3 PhMABiBr 3 FAMAPbBr 3 and FAMAPbI 3 One or more of;
[0051] S4: Based on S3, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is coated by spraying, spin coating or scraping as a hole transport layer; 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) is an important organic small molecule hole transport material, which is widely used in perovskite solar cells, and its CAS number is 207739-72-8; the thickness of the hole transport layer is controlled to be 5-30 nm;
[0052] S5: Based on S4, a layer of Au metal electrode is evaporated on the hole transport layer by evaporation, and the thickness of the metal electrode is controlled to be 10-1500nm.
[0053] In order to further improve product performance, step S2 in the above preparation process is further optimized by adding an organic dye to the weakly alkaline oxidant to enhance the light absorption capacity, thereby increasing the photocurrent value.
[0054] Specifically, step S2 is: in the above Ti 3 C 2 The MXene film was coated with a 0.01-0.4 ml / cm2 mixed aqueous solution of a weak alkaline oxidant and an organic dye, left to stand at room temperature for 0.5 h to 10 h, washed with water, and dried to obtain a partially oxidized Ti film. 3 C 2 / TiO 2 film, which serves as an electron transport layer.
[0055] The organic dye is at least one of Rhodamine B, Aniline Blue, Indigo and Phthalocyanine Blue.
[0056] In the mixed aqueous solution of the weak alkaline oxidant and the organic dye, the concentration of the weak alkaline oxidant is 0.1-1 mol / L and the concentration of the organic dye is 0.1-1 mol / L; preferably, the concentration of the weak alkaline oxidant is 0.2-0.4 mol / L and the concentration of the organic dye is 0.1-0.3 mol / L.
[0057] Photosensitization of organic dyes and TiO 2 The good energy level matching of the conduction band and the chemical promotion of Ti 3 C 2 Oxidation to form TiO 2 The excited electrons generated by organic dyes after absorbing visible light can be efficiently injected into TiO 2 The conduction band of TiO generated by NaOH treatment is improved, which improves the separation efficiency of carriers and reduces charge recombination. 2 The heterostructure acts as an electron transport layer, which can better extract carriers from the perovskite. These factors work together to optimize the interface charge dynamics, enhance the collection and transport of electrons, and thus significantly improve the overall photocurrent output.
[0058] In the specific embodiments and comparative examples, (Ti 3 C 2 T x )MXene thin layer dispersion, titanium carbide (Ti 3 C2 T x )MXene thin layer dispersion, item number: 104171, code number: XFK05-1, concentration 1 mg / ml, solvent: water, provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0059] Example 1
[0060] This embodiment is a schematic diagram of a novel perovskite X-ray direct detector, as shown in Figure 1 As shown, from bottom to top are substrate, electron transport layer, two-dimensional perovskite film, hole transport layer and metal electrode layer.
[0061] The above-mentioned novel X-ray direct detector preparation method:
[0062] S1: 2 ml of (Ti 3 C 2 T x )MXene thin layer dispersion was evenly coated on a 5×5 cm 2 The transistor driving circuit (TFT) was then transferred to a vacuum drying oven and dried at 60°C for 4 h to obtain Ti 3 C 2 MXene film.
[0063] S2: Prepare 1 ml of 0.5 mol / L NaOH aqueous solution and spray it on the Ti of S1 by spin coating. 3 C 2 The MXene film was placed on the surface of the film and allowed to stand for 6 h. The surface NaOH aqueous solution was removed by rinsing with deionized water. The film was then transferred to a vacuum drying oven and dried at 60 °C for 4 h to obtain a partially oxidized TiO2 film. 3 C 2 / TiO 2 film, which serves as an electron transport layer.
[0064] S3: Prepare a two-dimensional perovskite precursor solution: weigh 4.6 g of lead iodide, 1.6 g of methyl ammonium iodide and 2.35 g of phenethyl ammonium iodide, and dissolve them in 3 ml of polyvinylpyrrolidone to obtain a two-dimensional perovskite precursor solution.
[0065] S4: The two-dimensional perovskite precursor solution obtained in S3 is coated on the electron transport layer obtained in S2 by scraping, and then transferred to a vacuum drying oven and annealed at 120°C for 4 hours to obtain a two-dimensional perovskite film with a thickness of 500um.
[0066] S5: Based on S4, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is coated by spraying as a hole transport layer, and its thickness is controlled to be 15 nm.
[0067] S6: Based on S5, a layer of Au metal electrode is evaporated on the hole transport layer by an evaporation method, and its thickness is controlled to be 100 nm.
[0068] Comparative Example 1
[0069] This comparative example is a schematic diagram of a conventional perovskite X-ray direct detector, which includes, from bottom to top, a substrate, an electron transport layer, a two-dimensional perovskite film, a hole transport layer, and a metal electrode layer.
[0070] The above-mentioned novel X-ray direct detector preparation method:
[0071] S1: Spray 2 ml of 1 mg / ml titanium dioxide dispersion on a 5×5 cm 2 The transistor driving circuit (TFT) is then annealed at a temperature of 100° C. for 30 minutes to form an electron transport layer.
[0072] S2: Prepare a two-dimensional perovskite precursor solution: weigh 4.6 g of lead iodide, 1.6 g of methyl ammonium iodide and 2.35 g of phenethyl ammonium iodide, and dissolve them in 3 ml of polyvinylpyrrolidone to obtain a two-dimensional perovskite precursor solution.
[0073] S3: The two-dimensional perovskite precursor solution obtained in S2 is coated on the electron transport layer obtained in S2 by scraping, and then transferred to a vacuum drying oven and annealed at 120°C for 4 hours to obtain a two-dimensional perovskite film with a thickness of 500um.
[0074] S4: On the basis of S3, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was coated by spraying as a hole transport layer, and its thickness was controlled to be 15 nm.
[0075] S5: Based on S4, a layer of Au metal electrode is evaporated on the hole transport layer by an evaporation method, and its thickness is controlled to be 100 nm.
[0076] The results of this embodiment and comparative example are as follows:
[0077] Figure 2 The Ti prepared in this example is shown 3 C 2Scanning electron microscope (SEM) image of MXene film after being treated with NaOH solution. According to the figure, it can be observed that the treated Ti 3 C 2 The structure shows the characteristics of nanowire stacking. This nanowire structure not only helps to increase the surface area, but also promotes the migration of carriers in the film and improves the charge collection efficiency. The two-dimensional characteristics and excellent conductivity of MXene materials enable them to play a key role in the electron transport layer, providing a good foundation for the subsequent photoelectric conversion process.
[0078] Figure 3 The X-ray diffraction (XRD) spectrum clearly shows that Ti 3 C 2 After NaOH treatment, its surface has been effectively oxidized to TiO 2 The diffraction peaks observed in the XRD spectrum are all attributed to TiO 2 The characteristic peaks of TiO 2 The formation of TiO is successful. This oxidation process not only changes the surface chemical properties of the material, but also enhances its electron transport capacity. 2 As the electron transport layer, its role is crucial. Its excellent electronic conductivity can effectively reduce interface defects and promote the effective collection of carriers.
[0079] Figure 4 The photocurrent curves of the novel X-ray direct detector prepared in Example 1 and the conventional detector in Comparative Example 1 under X-ray irradiation switching are shown. By comparison, it can be seen that the photocurrent value of the novel detector in Example 1 is about 122nA, which is significantly higher than the photocurrent value of the conventional detector in the comparative example. This significant difference indicates that the in-situ generated TiO 2 The electron transport layer exhibits excellent ability in carrier extraction, greatly improving the photoelectric conversion efficiency of perovskite films.
[0080] This improvement is mainly due to several factors. First, TiO 2 The heterostructure with MXene can enhance the interface coupling and reduce the interface defects, thus improving the migration efficiency of carriers. 2 The formation of TiO provides a more ideal electric field environment for the perovskite layer, which is conducive to the rapid collection and transmission of electrons and reduces the probability of carrier recombination. In addition, the high carrier mobility of the perovskite film itself and the TiO 2 The combination of electron transport layer effectively improves the overall performance of the device.
[0081] In summary, Ti treated with NaOH 3 C 2The structure of MXene film and TiO formed by oxidation 2 layers, together forming an efficient electron transport network, providing theoretical support and practical basis for improving the photoelectric performance of perovskite X-ray direct detectors.
[0082] Example 2
[0083] This embodiment is a schematic diagram of a novel perovskite X-ray direct detector, which includes, from bottom to top, a substrate, an electron transport layer, a two-dimensional perovskite film, a hole transport layer, and a metal electrode layer.
[0084] The above-mentioned novel X-ray direct detector preparation method:
[0085] S1: 1 ml of (Ti 3 C 2 T x )MXene thin layer dispersion was coated on the conductive glass by spin coating, and then transferred to a vacuum drying oven and dried at 60℃ for 4h to obtain Ti 3 C 2 MXene film.
[0086] S2: Spray 1 ml of water directly onto the Ti of S1. 3 C 2 The MXene film was placed on the surface of the film and allowed to stand for 48 hours. The film was then transferred to a vacuum drying oven and dried at 60 °C for 4 hours to obtain a partially oxidized Ti 3 C 2 / TiO 2 film, which serves as an electron transport layer.
[0087] S3: Prepare a two-dimensional perovskite precursor solution: weigh 5.6 g of lead iodide, 2.2 g of formamidine hydroiodide and 2.6 g of tetrabutylammonium iodide, and dissolve them in 3 ml of DMF to obtain a two-dimensional perovskite precursor solution.
[0088] S4: The two-dimensional perovskite precursor solution obtained in S3 is coated on the electron transport layer obtained in S2 by scraping, and then transferred to a vacuum drying oven and annealed at 150°C for 4 hours to obtain a two-dimensional perovskite film with a thickness of 500um.
[0089] S5: Based on S4, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is coated by spraying as a hole transport layer, and its thickness is controlled to be 15 nm.
[0090] S6: Based on S5, a layer of silver metal electrode is evaporated on the hole transport layer by an evaporation method, and its thickness is controlled to be 100 nm.
[0091] Comparative Example 2
[0092] This comparative example is a schematic diagram of a conventional perovskite X-ray direct detector, which includes, from bottom to top, a substrate, an electron transport layer, a two-dimensional perovskite film, a hole transport layer, and a metal electrode layer.
[0093] The above-mentioned novel X-ray direct detector preparation method:
[0094] S1: Spray 1 ml of 1 mg / ml titanium dioxide dispersion on the transistor driving circuit (TFT) for 1 min, and then perform annealing at 100° C. for 30 minutes to prepare an electron transport layer.
[0095] S2: Prepare a two-dimensional perovskite precursor solution: weigh 5.6 g of lead iodide, 2.2 g of formamidine hydroiodide and 2.6 g of tetrabutylammonium iodide, and dissolve them in 3 ml of DMF to obtain a two-dimensional perovskite precursor solution.
[0096] S3: The two-dimensional perovskite precursor solution obtained in S2 is coated on the electron transport layer obtained in S1 by scraping, and then transferred to a vacuum drying oven and annealed at 150°C for 4 hours to obtain a 2D perovskite film with a thickness of 500um.
[0097] S4: On the basis of S3, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was coated by spraying as a hole transport layer, and its thickness was controlled to be 15 nm.
[0098] S5: Based on S4, a layer of silver metal electrode is evaporated on the hole transport layer by an evaporation method, and its thickness is controlled to be 100 nm.
[0099] The results of Example 2 and Comparative Example 2 further demonstrate the performance improvement of the perovskite X-ray direct detector. Figure 5 Ti 3 C 2 After the MXene film was treated with aqueous solution, the TiO 2 It presents a stacked granular structure. This granular TiO 2 The structure not only increases the specific surface area of the material, but also provides more channels for the migration of carriers, which helps to improve the charge collection efficiency.
[0100] Figure 6The photocurrent curves of the novel X-ray direct detector prepared in Example 2 and the conventional detector in Comparative Example 2 under X-ray irradiation switching are shown in FIG. It can be observed that the photocurrent value of the novel detector in Example 2 is about 23 nA, which is significantly higher than that of the conventional detector in Comparative Example 2. This result shows that the in-situ generated TiO 2 The electron transport layer exhibits excellent ability in extracting carriers from the two-dimensional perovskite layer, thereby significantly improving the photoelectric conversion efficiency of the perovskite film.
[0101] In this Example 2, water plays an extremely important role as a weak alkaline oxidant. Its role and advantages are mainly reflected in environmental friendliness and mild reaction conditions. As a common solvent, water not only reduces the risk of environmental pollution, but also has abundant sources and low prices, making the process more sustainable and economical. In addition, the use of water allows the oxidation process to be carried out under relatively mild conditions, which helps to maintain the Ti 3 C 2 The two-dimensional structure of MXene and its excellent conductivity avoid the potential damage to the material by high temperature or strong acidic environment, thus preserving its physical and chemical properties. Water also promotes surface passivation during the treatment process, forming a film layer that effectively reduces surface defects and enhances the stability and durability of the material. At the same time, water as a solvent can better control the TiO 2 The particle size and morphology of the TiO2 were optimized by adjusting the solution concentration and treatment time. 2 The close contact between particles helps to form a more connected electron transport network, improve the mobility of carriers, reduce the possibility of recombination, and thus improve the photoelectric performance of the detector. 2 The good interface contact between the layer and the perovskite layer significantly enhances the effective extraction of carriers, improves the separation efficiency of electrons and holes, and further improves the overall photoelectric conversion efficiency of the detector.
[0102] Example 3
[0103] Example 3 is a new type of perovskite X-ray direct detector, and the preparation method is the same as that of Example 1, with the only difference being step S2.
[0104] The S2 step of Example 3 is as follows:
[0105] S2: Prepare 1 ml of aqueous solution of NaOH and organic dye and spray it on the Ti of S1 by spin coating. 3 C 2 The MXene film was placed on the surface of the film and allowed to stand for 6 h. The surface NaOH and organic dye aqueous solution were washed with deionized water to remove the aqueous solution. The film was then transferred to a vacuum drying oven and dried at 60 °C for 4 h to obtain a partially oxidized TiO2 film.3 C 2 / TiO 2 film, which serves as an electron transport layer.
[0106] In the aqueous solution of NaOH and organic dye, the content of NaOH is 0.3 mol / L; the organic dye is aniline blue (CAS No.: 28631-66-5), and the content is 0.2 mol / L.
[0107] Comparative Example 3
[0108] Comparative Example 3 is a new type of perovskite X-ray direct detector, and the preparation method is the same as that of Example 1, with the only difference being step S2.
[0109] The S2 step of Comparative Example 3 is as follows:
[0110] S2: Prepare 1 ml of organic dye aqueous solution and spray it on the Ti of S1 by spin coating. 3 C 2 The MXene film was placed on the surface of the film and allowed to stand for 6 h. The aqueous solution of organic dyes on the surface was washed with deionized water and then transferred to a vacuum drying oven and dried at 60 °C for 4 h to obtain a partially oxidized Ti film. 3 C 2 / TiO 2 film, which serves as an electron transport layer.
[0111] In the aqueous solution of the organic dye, the organic dye is aniline blue (CAS No.: 28631-66-5) and the content is 0.5 mol / L.
[0112] like Figure 7 As shown, the results of Example 3 and Comparative Example 3 further demonstrate the performance improvement of the perovskite X-ray direct detector. The photocurrent value of the new detector in Example 3 is about 140nA, which is significantly higher than the detector in Comparative Example 3 and also significantly higher than Example 1. This shows that the photosensitive material added to the electron transport layer can further increase the photoelectric conversion efficiency.
[0113] The above experiments show that the combined use of aniline blue and NaOH in the electron transport layer significantly increases the photocurrent value. This synergy is due to the photosensitization of aniline blue and the interaction of TiO 2 The energy level of the conduction band matches. Aniline blue absorbs visible light to generate excited electrons, which can be efficiently injected into TiO 2 This process improves the separation efficiency of carriers and reduces the recombination of charges, thereby improving the photoelectric conversion efficiency. At the same time, the chemical action of NaOH promotes the 2 Oxidation to form TiO 2, improving the structure of the electron transport layer and further enhancing the collection and transport of electrons. Therefore, the synergistic effect of aniline blue and NaOH optimizes the interfacial charge dynamics and significantly improves the overall photocurrent output.
[0114] In summary, compared with the prior art, the present invention has significant advantages. First, the coated Ti 3 C 2 In-situ oxidation of the MXene film surface to generate TiO 2 The film acts as an electron transport layer, forming a Ti 3 C 2 / TiO 2 This structure not only retains the TiO 2 The superior properties in electron transport also have the toughness and good interface contact of MXene film, which effectively enhances the interface coupling between the electron transport layer and the two-dimensional perovskite film and significantly reduces the generation of interface defects. 3 C 2 TiO formed by in-situ oxidation on the MXene surface 2 The network is a composite structure that is both mechanically stable and exhibits excellent optoelectronic properties. 2 The design of the network as an n-type charge collector enables the effective extraction of carriers in the two-dimensional perovskite layer, and constructs a pin diode structure through the p-type top electrode, successfully realizing the current-voltage characteristics of rectification. This innovative structure effectively solves the limitation problem caused by organic components in the charge collection process, greatly improving the optoelectronic performance and response speed of the device. In addition, Ti 3 C 2 MXene, with its unique two-dimensional nanosheet structure, can achieve better interface contact with the substrate by virtue of its excellent film-forming property and compactness, thereby promoting efficient transfer of electrons from the electron transport layer to the substrate. Finally, the operation process of the present invention is simple, practical, and has a wide source of raw materials, which has the potential to achieve large-scale production. In addition, the constructed three-dimensional heterostructure X-ray detector exhibits excellent performance, good sensitivity and stability, and shows broad market application prospects.
Claims
1. A perovskite X-ray direct detector, whose structure from bottom to top is a substrate, an electron transport layer, a two-dimensional perovskite film, a hole transport layer and a metal electrode layer, characterized in that: The electron transport layer is an in-situ oxidized TiO2 matrix on a Ti3C2MXene film.
2. The perovskite X-ray direct detector according to claim 1, characterized in that: The electron transport layer is prepared by the following method: The substrate is coated with a Ti3C2MXene film and oxidized with a weakly alkaline oxidant solution to obtain a Ti3C2 / TiO2 film with a partially oxidized surface.
3. The perovskite X-ray direct detector according to claim 2, characterized in that: The electron transport layer is prepared by the following method: 0.03ml-0.1ml (Ti3C2T x )MXene thin layer dispersion, drying to obtain Ti3C2MXene film; The (Ti3C2T x ) The concentration of the MXene thin layer dispersion is 0.1 mg / ml-20 mg / ml; 10ml-250ml of weak alkaline oxidant solution is coated on the above-mentioned Ti3C2MXene film, left to stand at room temperature for 0.5h-72h, washed with water, and dried to obtain a Ti3C2 / TiO2 film with a partially oxidized surface.
4. The perovskite X-ray direct detector according to claim 2, characterized in that: The weak alkaline oxidant solution is an aqueous solution of one or more of LiOH, NaOH and KOH, with a molar concentration of 0.2-2 mol / L; or, the weak alkaline oxidant solution is water or hydrogen peroxide.
5. The method for preparing a perovskite X-ray direct detector according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: 0.03ml-0.1ml (Ti3C2T x )MXene thin layer dispersion, vacuum drying at 50-70°C for 2-6h to obtain Ti3C2MXene film; S2: coating the Ti3C2MXene film with a weak alkaline oxidant solution of 0.01-0.4 ml / cm2, standing at room temperature for 0.5h-72h, washing with water, and drying to obtain a Ti3C2 / TiO2 film with a partially oxidized surface layer, which is used as an electron transport layer; S3: coating a 2D perovskite film on the electron transport layer of S2 to obtain a two-dimensional perovskite film; S4: Based on S3, a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is coated as a hole transport layer by spraying, spin coating or blade coating; S5: Based on S4, a layer of Au metal electrode is evaporated on the hole transport layer by evaporation.
6. The method for preparing the perovskite X-ray direct detector according to claim 5, characterized in that: The S3 step is specifically as follows: coating the 2D perovskite aqueous solution on the electron transport layer by spraying, spin coating or scraping, and then transferring it to a vacuum drying oven, annealing at 180-220° C. for 3-5 hours, to obtain the two-dimensional perovskite film.
7. The method for preparing a perovskite X-ray direct detector according to claim 5, characterized in that: When the weak alkaline oxidant solution is an aqueous solution of one or more of LiOH, NaOH and KOH, the solution is allowed to stand at room temperature for 0.5 h to 10 h; when the weak alkaline oxidant solution is water, the solution is allowed to stand at room temperature for 36 h to 96 h.
8. The method for preparing a perovskite X-ray direct detector according to claim 5, characterized in that: The 2D perovskite is one or more of CF3PhMAPbBr3, CF3PhEAPbI3, BAMAPbI3, CF3PhAPbBr3, CF3PhEAPbBr3, CF3PhMASnBr3, CF3PhMABiBr3, FAMAPbBr3 and FAMAPbI3.
9. The method for preparing a perovskite X-ray direct detector according to claim 5, characterized in that: The thickness of the two-dimensional perovskite film is 100-1000um; the thickness of the hole transport layer is 5-30nm; and the thickness of the metal electrode is 10-1500nm.
10. Use of the perovskite X-ray direct detector according to any one of claims 1 to 4 in perovskite X-ray direct detection.